From Resistance to Resilience: Teachers' Adaptation Process to Mediating Digital Devices in Pre-COVID-19, during COVID-19, and Post-COVID-19 Classrooms in Nepal - Dirgha Raj Joshi; Jeevan Khanal; Ram Hari Dhakal (MDPI AG, 2023)
This qualitative study explores the implementation and adoption process of the use of digital devices and tools in teaching and learning before, during, and after the COVID-19 pandemic in Nepal. Using Rogers' diffusion of innovation theory as a framework, the study examines the adoption and adaptation of digital devices by in-service secondary mathematics teachers (n = 62) and the teachers' perceptions of and preferences for instructional modalities. The findings suggest that, despite the increased reliance on digital devices during the pandemic, there is a lower likelihood of them being used in face-to-face classrooms in developing countries, such as Nepal. The adoption of online learning had not yet reached the adoption stage, even after the onset of the COVID-19 pandemic. Prior to the pandemic, online learning was not widely adopted by teachers in developing countries societies. The study also provides important insights into the challenges of and opportunities provided by using digital devices in post-COVID-19 classrooms, and its implications for policymakers and educators in Nepal.